MAJLIS DZIKIR DAN SHOLAWAT SEBAGAI BASIS PENGEMBANGAN PENDIDIKAN ISLAM DI MASYARAKAT - Iskandar, Khusnan (MIYAH : Jurnal Studi Islam, 2024)
This study discusses about Majlis dzikir and Sholawat as a basis for the development of Islamic education in the community, with a focus on IPNU and IPPNU youth in Bambang Turi Village, Lamongan. The approach used is qualitative research through observation, interviews, and documentation. The results of the study show that Majlis dzikir and Sholawat not only function as a forum for ritual worship, but also as a means of character and spiritual education for adolescents. The participation of teenagers in this activity has a positive impact on their understanding of Islamic teachings, strengthens moral values, and increases awareness of the importance of togetherness in social life. In addition, this council is also a space for moral development and improvement of social skills through interaction with religious leaders and fellow community members. The role of Majlis dzikir and Sholawat in the development of Islamic education is further strengthened by the guidance of scholars and educators who convey Islamic values systematically and applicatively. Thus, this council contributes to shaping the religious character of adolescents and strengthening their Islamic identity in the midst of the challenges of globalization.